Embodied cognition. Sensitive sketching as a technique for recognizing architectural space - Bizzotto, Lucas (Estoa. Journal of the Faculty of Architecture and Urbanism, 2022)
Technologies have an impact on our way of living, of inhabiting and, above all, of knowing. Many activities that imply a bodily skill have been replaced by mechanical substitutes. The aim of this paper is to explore the bodily dimension of a specific relationship between technique and architecture. In this context, it focuses on the analysis and characterization of the cognition involved in the act of drawing the lived architectural space. It attempts to defend the view that drawing by hand develops a particular way of bodily cognition that brings together a set of perceptual actions and movements that enable a deeper recognition of the architectural space. Methodologically, the work is specified as a theoretical reflection and discussion where aspects of phenomenological philosophy and North American pragmatism, such as skills, bodily technical mastery, tacit knowledge and extended proprioception, are reviewed.